Comparative Performance of the Resilience Inventory (IRES) and Resilience Scale-14 (RS-14) Spanish Versions Among Postpartum Adolescent Mothers - Rojas Perez, Oscar F. (2022)
We sought to evaluate the psychometric properties of two resilience scales; the Resilience Inventory (IRES) and the 14-item Resilience Scale (RS-14) among Peruvian postpartum adolescent mothers. This cross-sectional study included 785 adolescent mothers who delivered at a maternity hospital in Lima, Peru. The Spanish versions of IRES and RS-14 were used to evaluate the properties of the measures. We examined reliability using Cronbach’s alpha. We used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to assess the construct validity and factor structures of the two scales. Both scales had good internal consistency (Cronbach’s alpha > 0.7). Correlation between IRES and RS-14 scores was fair (r = 0.53). The EFA results of both scales yielded a three-factor structure. EFA including all items from IRES and RS-14 yielded a six-factor structure. CFA results corroborated the original seven-factor structure for IRES and yielded measures indicating a good level of goodness of fit (comparative fit index of 0.93) and accuracy (root mean square error of approximation of 0.07). Overall, Spanish language versions of both the IRES and the RS-14 are reliable and valid scales for assessing resilience among Peruvian postpartum adolescent mothers. Additional research is needed to integrate culturally-specific traits into resilience measures.